GLOBAL PERSPECTIVES ON ELECTRIC VEHICLE ADOPTION AND ENVIRONMENTAL BENEFITS - V Neeraja, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The increasing environmental degradation and India's heavy reliance on fuel imports have necessitated a shift towards sustainable transportation solutions. Motivated by the urgent need to reduce carbon emissions and achieve energy security, this study explores the role of Electric Vehicles (EVs)—specifically Battery Electric Vehicles (BEVs), Hybrid Electric Vehicles (HEVs), and Plug-in Hybrid Electric Vehicles (PHEVs)—in enhancing sustainable transportation in India. Using the Diffusion of Innovation (DOI) theory as the theoretical framework, the research examines how Indian consumers' adoption patterns are influenced by environmental consciousness, economic viability, and technological readiness. Given India's unique climate conditions and urbanisation patterns, the study evaluates the suitability and long-term impact of EVs in the Indian context. A structured questionnaire was administered across metropolitan and Tier 2 cities, and the data were analysed using statistical tools such as descriptive statistics, exploratory factor analysis (EFA), regression analysis, and structural equation modelling (SEM). The findings aim to offer empirical perspectives on the drivers and barriers of EV adoption, offering policy implications for enhancing the diffusion of EV technologies. This research highlights the transformative potential of EVs not only for sustainable transportation but also for India's broader climate resilience and energy independence agenda.